Effects of Superhydrophobic Coating on the Water Uptake, Droplet Dispersion, and Bacterial Adhesion in Cotton Masks - Cortez, Gershon Mark G.; Botabara-Yap, Mary Jane; Yllano, Orlex B. (8ISC Abstract Proceedings, 2022)
Numerous microorganisms can be transmitted via coughing, sneezing, and even talking, and since oral and respiratory droplets are water-based, it is necessary for a mask, especially on its external layer, to have some degree of water repellency. The surgical mask is the standard mask against respiratory droplets. However, due to the increasing demand for surgical masks, shortage and possible environmental implications may urge the public to use an alternative mask with efficacy against water-based droplets close to the surgical mask. Using posttest only control groups research design, cotton masks were coated with a superhydrophobic coating (SHC) and evaluated for their efficacy to prevent water uptake, block dispersed droplets, and reduce bacterial adhesion, using the uncoated cotton mask and surgical mask for comparisons. The experiment results revealed that the water uptake of the cotton mask with SHC (6.45%) was significantly lower than the uncoated cotton masks (109.14%) but was significantly higher than the surgical mask (3.26%), both at p < 0.001. Also, a significantly lower number (p = 0.001) of adhered bacteria (from 5666.67 CFU/cm2 to 2166.67 CFU/cm2) was collected from cotton masks after the addition of SHC. Moreover, there was no significant difference in the bacterial adhesion between cotton masks with SHC and surgical masks (p = 0.238). In droplet dispersion, there was no significant difference among the three types of masks observed (p=0.128). Overall, the superhydrophobic coating can make cotton masks produce efficacy against respiratory droplets that is almost similar to surgical masks. It is recommended that when opting to use a substitute for a surgical mask, it is recommended to use a two-layer cotton mask coated with superhydrophobic material. Keywords : cotton mask, superhydrophobic coating, water uptake, droplet dispersion, bacterial adhesion